2022
DOI: 10.7759/cureus.22163
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Radiological Profile and Outcome of Airway Foreign Body Aspiration in Children: A Single-Center Experience From a Tertiary Care Center in Eastern India

Abstract: BackgroundForeign body aspiration is one of the leading causes of childhood morbidity and mortality among older infants and toddler age groups. Missed and delayed diagnosis of foreign body aspiration can lead to increased incidence of complications. Early diagnosis can prevent life-threatening complications and morbidity. In this study, we aimed to evaluate the clinical and radiological details, types, localization of foreign bodies, complications, and outcomes in pediatric patients who presented to our hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 18 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…The violent coughing bouts are followed by an asymptomatic period, after which persistent bothersome cough remains the main symptom. [ 1 ] The combination of cough and dyspnea is a late symptom associated with retained tracheobronchial foreign bodies. A meticulous history obtained from the parents and clinical suspicion is essential to diagnose foreign body aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The violent coughing bouts are followed by an asymptomatic period, after which persistent bothersome cough remains the main symptom. [ 1 ] The combination of cough and dyspnea is a late symptom associated with retained tracheobronchial foreign bodies. A meticulous history obtained from the parents and clinical suspicion is essential to diagnose foreign body aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The aspiration risk is higher in the 1–3 year age group due to their propensity for oral exploration, inadequately developed dentition and immature neuromuscular mechanisms of deglutition and airway protection. [ 1 , 2 ] Vegetative or organic foreign bodies such as ground nuts and peanuts account for about 75% of aspirated vegetable foreign bodies. [ 1 2 3 ] Tamarind seed aspiration is usually observed in kids from rural backgrounds, with easy access to tamarind fruits and their by-products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] A study found the highest mortality rate of up to 58.3% [34] as opposed to the lowest only 4.5%. [35] Less than 2% of patients in PICUs who were mechanically ventilated died overall in wealthy nations 2. Groups B and C had the highest death rates (33.3%), followed by group A (28.2%), however, this difference was statistically insignificant (p=0.064).…”
Section: Discussionmentioning
confidence: 99%
“…[24] Of the 22 children studied by Sai Akhil et al, 63.6% of the foreign bodies removed during bronchoscopies were found to be composed of organic components, with peanuts being the most often (31.8%). [25] Fidkowski et al found that most aspirated foreign bodies among children were formed of organic materials in a review of the literature on Research consistently shows that peanuts and other nuts, as well as seeds like sunflower and watermelon, were the most commonly aspirated foreign bodies. [26] Pneumomediastinum as a complication of FBA is a very rare condition among pediatrics.…”
Section: Discussionmentioning
confidence: 99%